Evaluation of treatment outcomes and risk factors of clinical non-improvement in patients with paraquat poisoning: A 10-year retrospective study - Harsimran Kaur, Vijayanarayana Kunhikatta, Shankar M Bakkannavar, Jayaraj Mymbilly Balakrishnan, Girish Thunga (Journal of Applied Pharmaceutical Science, 2025)
A 10-year retrospective study was conducted from 1st January, 2012 to 1st March, 2023 in patients admitted to a tertiary care hospital in South India with acute paraquat (PQ) poisoning. The primary objective of the study was to evaluate clinical outcomes in patients who received extracorporeal removal (ECR) treatment (ECR group) compared to those who did not (non-ECR group). A secondary objective was to assess risk factors associated with clinical non-improvement in these patients. Chi-square and Mann-Whitney tests were used to compare categorical and continuous variables, respectively; and multivariate logistic regression was employed for clinical non-improvement risk factor assessment. We included a total of 304 patients with a median (IQR) age of 25 (13.5) years. The clinical improvement rate was 29.3% (n = 89). There was no significant difference in clinical improvement between ECR and non-ECR treatment groups (p = 0.79). Increased aspartate transaminase (AST) levels (OR: 1.027; 95% CI: 1.011–1.043, p
Keywords: Paraquat poisoning, improvement, extra-corporeal removal, treatment